Using Canva Application for Elementary School Learning Media - Andika Guruh Saputra; Tia Rahmawati; Beatrix Andrew; Yazeed Amri (Yayasan Adra Karima Hubbi, 2022)
The purpose of this study is to develop learning media using the Canva application in elementary schools, for beginners and elementary school teachers who are used to create multimedia-based learning media as teaching materials that are used at this time, the declining quality of learning at this time especially in Elementary school level (SD), on this occasion we describe the use and utilization of the Canva application, the aim is to increase the interest and sympathy of teachers and students in learning and also to facilitate the process of understanding students' learning in schools so that it can be said that the quality of education in schools is perfect. On this basis, this Canva application has several interesting features to serve, including ready-to-use templates, icons and illustrations, text, background tips and tricks in using applications, animations, and duplication, over time and the use of technology. dependent on self i ourselves in taking advantage of it.